Regulating for gender-equitable decent work in social and community services: Bringing the state back in. (September 2021) - Macdonald, Fiona; Charlesworth, Sara
This article explores the potential of regulatory and policy reform for gender-equitable decent work in social and community services, a rapidly growing sector of female employment in many Organisation for Economic Co-operation and Development countries. Along with other feminised sectors, employment in this sector is marked by low rates of unionisation, poor pay and fragmented, insecure working hours. Internationally, gig economy work is now appearing in the sector. A distinguishing feature of the sector is employers' reliance on government funding through contracted services or via direct payments to individuals. The distance of government from accountability for workers in publicly funded services directly contributes to gendered undervaluation and poor working conditions. However, the presence of the state also provides options for regulatory reform. This article considers the different roles played by government, as employment regulator, as funding and bargaining actor and as market manager and care regulator. Adopting a broad conception of regulation, it canvasses options for bringing the state back in to address gender inequality and precarious work. In the Australian context, it examines potential for rebuilding state accountability for gender-equitable decent work in individualised social care in which the gender inequalities and poor working conditions present in social and community services are amplified.